Design and development of rocket based rubber hollow elastic ball launcher / Syahmie Arif Farhan Husariman - Husariman, Syahmie Arif Farhan (2022)
This Final year project consists of the design and development of rocket-based rubber hollow elastic ball launcher which launched vertical at fixed angle. The main reasons why the project should be done is to figure out a launcher with applied projectile motion. It is to make student easier to understand and applied the concepts through visualize learning. This project involved with launcher design that gives some flight data of experiment. By the end of this project, there are involves various methods such as the concept design, the designing, and fabrication process. After the manufacturing process done, the projectile launcher is tested to gain the flight data and solved by using projectile motion analysis equation. From there the projectile motion experiment and the objective for the experiment is succeed. For expected result, this project will design a projectile launcher by using solid modelling computer-aided design and fabricate it. From there, initial velocity calculated using projectile equation referred to the past project. As conclusion, this project can represent the application of projectile motion by using the projectile equation to find unknown value.